Planejamento urbano sustentável com foco na acessibilidade - Rocha, Vanessa Tibola da (2016)
Cities have significant changes in their urban space. The overcrowding in urban centers is evident, because today 54% of the world population lives in these areas. Thus, the lacks of current urban planning undermine sustainable development of cities. This is because hardly is expected quality housing, education, health, public spaces for leisure and employment opportunities to the people. Thus, the use of urbanland and the quality of life of individuals are compromised. In that sense, the inclusion of sustainable urban planning practices becomes indispensable tool to ensure the future of cities and the survival of man. This research aimed to identify and analyze sustainable urban planning indicators for the state of Rio Grande do Sul, considering three cities polo south-rio-grandeas the basis of the research, namely: Porto Alegre, Santa Maria and Passo Fundo, with focus on accessibility. As research methodology, the following steps were developed: identification of sustainable urban planning indicators in environmental, social and economic. Then diagnoses were made of the study areas, which were identified its problems and potential - with regard to the current urban planning. Based on this analysis, identified sustainable urban planning practices. Still, according to the central objective of the work (accessibility), there was the lifting of sidewalks quality index in the city of Passo Fundo. The assessment methodology of the index was applied through the perception of the users of the roads according to the level of importance of seven indicators of sustainable sidewalks and technical evaluation of these indicators in the study area. The results indicate that there is need to expand the green areas in the study sites. Still, the quality score of sidewalks in Passo Fundo was identified asvery bad (G - 1.92). However, the survey provided an opportunity critical analysis of the urban planning process of the cities involved and triggered concepts in the management process, focusing on a more sustainable development aimed at the importance of the public tour for sustainable urban planning.